Antiplasmodial Properties and Bioassay-Guided Fractionation of Ethyl Acetate Extracts from Carica papaya Leaves - Paula Melariri; William Campbell; Paschal Etusim; Peter Smith (Journal of Parasitology Research)
We investigated the antiplasmodial properties of crude extracts from Carica papaya leaves to trace the activity through bioassay-guided fractionation. The greatest antiplasmodial activity was observed in the ethyl acetate crude extract. C. papaya showed a high selectivity for P. falciparum against CHO cells with a selectivity index of 249.25 and 185.37 in the chloroquine-sensitive D10 and chloroquine-resistant DD2 strains, respectively. Carica papaya ethyl acetate extract was subjected to bioassay-guided fractionation to ascertain the most active fraction, which was purified and identified using high-pressure liquid chromatography (HPLC) and GC-MS (Gas chromatography-Mass spectrometry) methods. Linoleic and linolenic acids identified from the ethyl acetate fraction showed IC50 of 6.88 μg/ml and 3.58 μg/ml, respectively. The study demonstrated greater antiplasmodial activity of the crude ethyl acetate extract of Carica papaya leaves with an IC50 of 2.96±0.14 μg/ml when compared to the activity of the fractions and isolated compounds.